Effect of Temperature and Host Density on the Rate of Increase of Bracon brevicornis Wesmael (Hymenoptera: Braconidae). - Subba Rao, B. R.; Kumar, S. S. (Contributions to Entomology = Beiträge zur Entomologie, 1960)
1. Host density had no significant effect on oviposition of the parasite and it laid more or less a constant number of eggs under the conditions of the experiments and in the given time period. - 2. Host utilization did not depend upon the density of the host but upon absolute number of hosts available to the parasite in a given universe (this being within the limits of its search). - 3. A female parasite distributed its progeny to the very best advantage when the number of hosts in the environment was 10-15. - 4. The efficiency for distribution of the progeny to the best advantage upon the hosts available was impaired and greater super-parasitism occurred when the host number supplied was very low. - 5. The physiological conditions of the parasite and not the host density controlled the rate of increase of the parasite per unit of time. - 6. At 35°C maximum number of eggs was laid by the parasite but the faculty to distribute them efficiently was impaired. - 7. 25-30°C was the optimum temperature for best distribution of the progeny.